Interactive questioning in critical care during handovers: a transcript analysis of communication behaviours by physicians, nurses and nurse practitioners. Issue 6 (13th December 2013) - Rayo, Michael F; Mount-Campbell, Austin F; O'Brien, James M; White, Susan E; Butz, Alexandra; Evans, Kris; Patterson, Emily S
Abstract : Objective: Although there is a growing recognition of the importance of active communication behaviours from the incoming clinician receiving a patient handover, there are currently no agreed-upon measures to objectively describe those behaviours. This study sought to identify differences in incoming clinician communication behaviours across levels of clinical training for physicians and nurses. Methods: Handover observations were conducted during shift changes for attending physicians, resident physicians, registered nurses and nurse practitioners in three medical intensive care units from July 2011 to August 2012. Measures were the number of interjections from the incoming clinician and the communication mode of those interjections. Each collaborative cross-check, a specific type of interactive question, was subsequently classified by level of assertiveness. Results: 133 patient handovers were analysed. Statistical differences were found in both measures. Higher levels of training were associated with fewer interjections, and a higher proportion of interactive questioning to detect erroneous assessments and actions by the incoming provider. All groups were observed to use the least assertive level of a collaborative cross-check, which contributed to misunderstandings. Nurses used less assertive collaborative cross-checks than physicians. Conclusions: Differences across clinician type and levels of clinical training were found in both measures during patient handovers. The findings suggest that training could enable physicians and nurses to learn communication competencies during patient handovers which were used more frequently by more experienced practitioners, including interjecting less frequently and using interactive questioning strategies to clarify understanding, and assertively question the appropriateness of diagnoses, treatment plans and prognoses. Accompanying cultural change initiatives might be required to routinely employ these strategies in the clinical setting, particularly for nursing personnel.